2019
DOI: 10.1136/openhrt-2019-001016
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of sST2 in patients with mitral annulus disjunction and ventricular arrhythmias

Abstract: ObjectiveDisplacement of the mitral valve, mitral annulus disjunction (MAD), is described as a possible aetiology of sudden cardiac death. Stress-induced fibrosis in the mitral valve apparatus has been suggested as the underlying mechanism. We aimed to explore the association between stretch-related and fibrosis-related biomarkers and ventricular arrhythmias in MAD. We hypothesised that soluble suppression of tumourigenicity-2 (sST2) and transforming growth factor-β1 (TGFβ1) are markers of ventricular arrhythm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
3
19
0
4
Order By: Relevance
“…sST2 is an interleukin 1 receptor family member secreted by cardiac cells in circumstances of biomechanical stress that can promote myocardial fibrosis. In the present work, sST2 was enhanced in patients with MAD and ventricular arrhythmias (p=0.01) and improved the differentiation of patients with and without ventricular arrhythmia in conjunction with LV, EF and papillary muscles LGE 11…”
supporting
confidence: 57%
“…sST2 is an interleukin 1 receptor family member secreted by cardiac cells in circumstances of biomechanical stress that can promote myocardial fibrosis. In the present work, sST2 was enhanced in patients with MAD and ventricular arrhythmias (p=0.01) and improved the differentiation of patients with and without ventricular arrhythmia in conjunction with LV, EF and papillary muscles LGE 11…”
supporting
confidence: 57%
“…A familial distribution of MVP has been largely documented especially in Barlow’s patients [ 16 , 17 ] and four genes are known so far to be linked to MVP; interestingly, also an association of isolated MVP and mutations in cardiomyopathy genes was observed, further supporting the important role of myocardial involvement in the disease [ 18 , 19 ]. Finally, the possibility of testing specific biomarkers might be offered in the future; for example, initial observations showed the soluble suppression of tumourigenicity-2-serum level (sST2), as a marker of the stretched myocardium, to be higher in patients with mitral annular disjunction and VA [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrary to the study of Patton et al, they found normal NT-proBNP and CRP levels in their population. In the same study TGFß1 was assumed to be responsible for the ventricular arrhythmogeneity (Scheirlynck et al, 2019). In the Physicians' Health Study a positive correlation was reported between high serum CRP levels and increased arrhythmia risk vulnerability, however in the Nurse's Health Study population similar connection could not be proven (Balla et al, 2019).…”
Section: Laboratory Opportunities For Predicting Ventricular Arrhythmiasmentioning
confidence: 97%